TEST OF ENGLISH FOR AVIATION PERSONNEL TO MEET ICAO LANGUAGE PROFICIENCY REQUIREMENTS - Petrashchuk, Olena (Proceedings of National Aviation University, 2012)
The article is devoted to the actual problem of the assessment of English language proficiency of aviation personnel. The paper presents an English language test, which is used for professional pilots and air traffic controllers.